2004
DOI: 10.1111/j.1600-6143.2004.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4 and P-Glycoprotein Activity in Healthy Controls and Transplant Patients on Cyclosporin vs. Tacrolimus vs. Sirolimus

Abstract: This study aimed to determine the impact of maintenance immunosuppressive therapy with cyclosporin A (CsA), tacrolimus (FK506) and sirolimus (Rapa) on the in vivo activity of both intestinal and hepatic cytochrome P450 3A4 (CYP3A4) and P-glycoprotein (PGP) in renal transplant patients. The activity of these four elimination pathways was measured by the recently validated intravenous (iv) and per oral (po) 14 C erythromycin breath and urine test. In addition, overall hepatic P450 activity was measured by the 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Due to the numerous adverse effects, narrow safety margin and large intra-and inter-individual variability in pharmacokinetics, therapeutic monitoring is mandatory [1][2][3] . The normal pharmacokinetic curve of tacrolimus has a peak-andtrough pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the numerous adverse effects, narrow safety margin and large intra-and inter-individual variability in pharmacokinetics, therapeutic monitoring is mandatory [1][2][3] . The normal pharmacokinetic curve of tacrolimus has a peak-andtrough pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its narrow therapeutic index, optimal dosing with therapeutic monitoring is necessary. Tacrolimus is mainly metabolized by cytochrome P450-3A in the liver and a substrate of P-glycoprotein, an efflux pump, in both liver and intestine [2,3] . The inhibition of P450-3A and P-glycoprotein can slow down its metabolism and ketoconazole is such a potent inhibitor.…”
Section: World Journal Of Nephrologymentioning
confidence: 99%
“…The alteration in these enzymes and proteins affects drug bioavailability and increases the risk for adverse drug reactions (Dreisbach and Lertora 2008;Dreisbach 2009). In transplant patients on cyclosporine-A or tacrolimus, studies have shown changes in both CYP3A4 and P-glycoprotein activity in healthy controls and patients (Lemahieu WP, 2004). In addition to the condition or disease alone regulating enzyme activity and transporter expression, consideration should be applied during treatment for patients on multiple medications (van der Deen M, 2005).…”
Section: Patient Health Status Dictate Drug Dispositionmentioning
confidence: 99%
“…For several years, the mammilian target of rapamycin (mTOR) inhibitor, sirolimus (Rapamune®), has also been used as an immunosuppressive drug in organ transplantation. Similar to ciclosporin, it is also metabolized in bowel and liver by cytochrome P450 3A [1] . The main advantage of sirolimus is its virtual lack of nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Both are calcineurin-inhibitors and have the same mode of action. They are mainly metabolized by cytochrome P450 3A4 in bowel and liver [1] . The main side effects of ciclosporin and tacrolimus are renal toxicity, neurotoxicity, arterial hypertension, diabetes mellitus and hyperlipidemia [2] .…”
Section: Introductionmentioning
confidence: 99%